Changes in the Cutaneous Nerve Fiber Staining and Distribution of PGP9.5 in Clinically Uninvolved Skin in Leprosy Patients after Completion of Multidrug Therapy and Assessing PGP9.5 as a Marker of Treatment Response - Vishal Thakur; Tarun Narang; Anuradha Bishnoi; Garima Dhawan; Ankur Sharma; Uma Nahar Saikia; T Muhammad Razmi; Sunil Dogra; Sanjeev Handa; Manish Modi (Wolters Kluwer Medknow Publications, 2024)
Background: Subclinical involvement of nerves may sometimes be present much before the overt clinical manifestations become apparent. Protein gene product (PGP) 9.5, a ubiquitin-C-terminal hydrolase, has been widely used as a marker to study the involvement of peripheral nerve fibers in many diseases. Aim and Objectives: To evaluate the change in cutaneous nerve fiber staining and distribution from pre-treatment and post completion of multidrug therapy through the expression of PGP9.5 and to assess PGP9.5 as a marker of treatment response. Materials and Methods: In this prospective single-center observational study, skin biopsy was taken in patients with leprosy, having areas of nerve function impairment (NFI), based on findings of nerve conduction studies (NCSs), but not having lesions or impaired tactile or thermal impairment clinically. The thin nerve fiber density in the clinically normal skin in areas supplied by nerve showing changes of sensory neuropathy was evaluated to study the density of the fibers. A second biopsy was taken at the end of treatment from a site near the previous site to assess the changes in intra-epidermal nerve fiber staining and distribution. Results: Thirty-three patients were recruited in the present study (24 males and 9 females). Pre-treatment, 27 patients had abnormal NCSs, while six patients did not have any evidence of neuropathy on NCSs. Staining for nerve fibers using PGP9.5; in the epidermis was positive in five patients pre-treatment and 11 patients post treatment (P = 0.181). Staining in the dermis revealed positivity in 14 pre-treatment, which increased to 18 post treatment (P = 0.342). Adnexae showed positivity in five patients pre-treatment and increased to 17 post treatment (P = 0.005). Conclusion: A reduced PGP9.5 staining in the epidermal, dermal, and adnexal regions was seen in leprosy patients, which improved post treatment. Thus, PGP9.5 may serve as a marker of NFI and treatment response.